On the Microstructure and Properties of Complex Concentrated bcc Solid Solution and Tetragonal D8m M5Si3 Silicide Phases in a Refractory Complex Concentrated Alloy - Nik Tankov; Claire Utton; Panos Tsakiropoulos (Alloys, 2024)
In this work, the refractory complex concentrated alloy (RCCA) 3.5Al–4Cr–6Ge–1Hf–5Mo–36Nb–22Si–1.5Sn–20Ti–1W (at.%) was studied in the as cast and heat treated conditions (100 h or 200 h at 1500 °C). There was strong macrosegregation of Si in the 0.6 kg button/ingot of the cast alloy, in which A2 solid solution, D8m βNb5Si3, C14-NbCr2 Laves phase and Tiss and a ternary eutectic of the A2, D8m and C14 phases were formed. The partitioning of Ti in the as cast and heat treated microstructure and its relationships with other solutes was shown to be important for the properties of the A2 solid solution and the D8m βNb5Si3, which were the stable phases at 1500 °C. The near surface microstructure of the alloy was contaminated with oxygen after heat treatment under flowing Ar. For the aforementioned phases, it was shown, for the first time, that there are relationships between solutes, between solutes and the parameters VEC, Δχ and δ, between the said parameters, and between parameters and phase properties. For the contaminated with oxygen solid solution and silicide, trends in relationships between solutes, between solutes and oxygen content and between the aforementioned parameters and oxygen content also were shown for the first time. The nano-hardness and Young’s modulus of the A2 solid solution and the D8m βNb5Si3 of the as cast and heat-treated alloy were measured using nanoindentation. Changes of nano-hardness and Young’s modulus of the A2 solid solution and D8m βNb5Si3 per solute addition for this multiphase RCCA were discussed. The nano-hardness and Young’s modulus of the solid solution and the βNb5Si3, respectively, were 9.5 ± 0.2 GPa and 177.4 ± 5.5 GPa, and 17.55 ± 0.5 GPa and 250.27 ± 6.3 GPa after 200 h at 1500 °C. The aforementioned relationships and properties of the two phases demonstrated the importance of synergy and entanglement of solutes, parameters and phases in the microstructure and properties of the RCCA. Implications of synergy and entanglement for the design of metallic ultra-high temperature materials were emphasised.